THE BRIDGING DIGITAL ENTREPRENEURIAL CAPABILITY AND BUSINESS PERFORMANCE: THE MEDIATING ROLE OF DIGITAL ENTREPRENEURIAL PRODUCT DEVELOPMENT EVIDANCE FROM MSMES IN CIANJUR - Ira Mariyah Ulfah; Wenny Djuarni; Denny Aditya Dwiwarman; Mohammad Sigit Adi Nugraha (Prosiding Amal Insani Foundation, 2026)
Purpose This study aims to analyze the impact of digital entrepreneurial capability on MSME business performance, with digital entrepreneurial product development as a mediating variable. Methodology: A quantitative approach was employed using a sample of 200 MSMEs in Cianjur, Indonesia, selected via purposive sampling criteria. Data were analyzed using structural equation modeling (SEM) via AMOS 22. The measurement model evaluation confirmed high reliability and validity, with Composite Reliability (CR) values ranging from 0.88 to 0.91 and Average Variance Extracted (AVE) between 0.59 and 0.62. Findings: The structural model results show that digital entrepreneurial capability significantly influences digital product development (β=0.63, CR=6.82, p<0.001). Digital product development also has a positive effect on business performance (β=0.47, CR=5.14, p<0.001). Furthermore, digital entrepreneurial capability maintains a direct significant effect on performance (β=0.29, CR=3.26, p=0.001, β=0.29, CR=3.26, p=0.001). Crucially, mediation analysis via bootstrapping confirms that digital product development serves as a significant partial mediator (indirect effect=0.30, p<0). Implication: These findings underscore that for MSMEs, possessing digital skills is insufficient without the ability to transform them into tangible digital products like catalogs and AI-assisted content. This study provides a strategic framework for community service programs to prioritize applied digital product output to ensure MSME sustainability.